[OP.2D.05] RELATIONSHIP OF OXIDATIVE STRESS WITH CARDIAC HYPERTROPHY IN HYPERTENSIVE PATIENTS. (September 2016) - Cottone, S.; Nardi, E.; Guarneri, M.; Guarino, L.; Altieri, D.; Cerasola, G.; Mulè, G.
Abstract : Objective: Left ventricular hypertrophy is common in hypertensive patients. In these subjects increased oxidative stress has been observed. Our aim was to evaluate the association of biomarkers of both oxidative stress and inflammation with markers of cardiovascular damage in a large group of hypertensives with different stages of renal function. Design and method: In 517 hypertensives we analyzed left ventricular mass indexed for body surface area, and we assayed plasma levels of 8-isoprostaglandin F2α and high sensitivity C reactive protein. Results: Multivariate analysis carried out considering left ventricular mass as dependent variable, and including 8-isoprostaglandin F2α, high sensitivity C reactive protein, age, sex, body mass index, estimated glomerular filtration rate, serum glucose, (log)triglycerides, hemoglobin, pulse pressure or systolic blood pressure, mean or diastolic blood pressure, and antihypertensive treatment showed that in hypertensives plasma levels of 8-isoprostaglandin F2α were correlated with left ventricular mass (β=0.269, p < 0.0001). The bivariate relationship of left ventricular mass with 8-isoprostaglandin F2α in hypertensives with estimated glomerular filtration rate higher and lower than 60 ml/min/1.73m2 was also calculated separately, demonstrating no significant differences in both correlations coefficients and slopes of the regression lines (r = 0.254, p < 0.001 and r = 0.226, p < 0.002; respectively). In the overall group, receiver operating characteristic curves showed that 8-isoprostaglandin F2α and high sensitivity C reactive protein were predictors of left ventricular hypertrophy, p < 0.0001. Conclusions: To the best of our knowledge, this is the first demonstration that in hypertensives oxidative stress is correlated to left ventricular hypertrophy independently of other confounding factors. Oxidative stress might participate in the development of hypertensive cardiac hypertrophy.